2009
DOI: 10.1053/j.seminoncol.2009.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Cancer: A Prototypic Tumor of Young Adults

Abstract: Testicular cancer is the most common solid tumor among males in the 20-39 year-old age range. Moreover, testicular cancer has unique biological associations, clinical features, and psychosocial impacts that establish this tumor as a prototypic malignancy of young adults. The biology of testicular germ cell tumors after puberty is distinctive. Epidemiologic patterns of testicular cancer suggest etiologic factors that may be congenital, racial, and geographic. The clinical management of a cancer common among you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 28 publications
2
74
0
Order By: Relevance
“…1 With cisplatin-based chemotherapy, 2 most patients with GCC will be long-term survivors, and their 5-year survival rate exceeds 90%. 3 However, it has recently been demonstrated that patients aged 40 years have a 2-fold higher GCC-specific mortality, 4 and it is hypothesized that reduced treatment intensity combined with increased treatmentrelated toxicity in this age group may be the explanation.…”
Section: Introductionmentioning
confidence: 99%
“…1 With cisplatin-based chemotherapy, 2 most patients with GCC will be long-term survivors, and their 5-year survival rate exceeds 90%. 3 However, it has recently been demonstrated that patients aged 40 years have a 2-fold higher GCC-specific mortality, 4 and it is hypothesized that reduced treatment intensity combined with increased treatmentrelated toxicity in this age group may be the explanation.…”
Section: Introductionmentioning
confidence: 99%
“…This type of testicular germ cell cancer is generally regarded as the most common cancer that occurs in men between the ages of 20 years and 40 years. 5 Tumors of this type are frequently hemorrhagic both clinically and pathologically. Microscopically, these tumors consist of cells that tend to be large and appear poorly differentiated or undifferentiated (embryonic).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the 5-year disease-free survival of patients with TGCTs is the highest amongst any other solid malignancy in males due to effective modern therapy, including platinum-based combination chemotherapy regimens, and close surveillance following surgery. In addition, the cure rate for patients with TGCTs is 95-96% (4,5). However, ~5% of patients with TGCTs still develop treatment resistance (6).…”
Section: Introductionmentioning
confidence: 99%